Conceptual Geological Model of the Ribeirão Tortinho Watershed, Federal District of Brazil (Modelo geológico conceitual da Bacia do Ribeirão Tortinho, Distrito Federal, Brasil) - Angelo, Tiago Valim; Sousa, Gustavo Evaristo de; Cunha, Luciano Soares da (Revista Brasileira de Geografia Física, 2019)
The increase of water consumption, associated with the disordered land occupation, lead to a scenario of overexploitation of surface and underground sources in the Federal District of Brazil. With the expansion of urban areas, the groundwater has played a major role in public supply, evidencing the need of deepening the knowledge of the local hydrogeologic framework. In this regard, this paper presents a conceptual hydrogeological model of the Córrego do Ribeirão Tortinho Watershed. The main goal of this report is to organize the available data and present it as a conceptual model that can subsidize the construction of a numerical groundwater flow model. In order to simplify the representation of the hydrogeologic framework, rocks and unconsolidated materials with similar hydraulic parameters and textural properties were grouped together to form hydrostratigraphic units. Six units were differentiated and their properties and attributes were discussed. The porous domain is represented by the hydrostratigraphic units I, II, III, and IV, characterized by oxisols, plintosols, cambisols, and gleisols, respectively. Rock units of the Paranoá Group were attributed to the other two hydrostratigraphic units. Quartzites and metarhytmites (Ribeirão da Contagem and Serra da Meia Noite Formations, respectively) form the hydrostratigraphic unit V, while slates (Ribeirão do Torto Formation) correspond to the unit VI. Through this systematic arrangement, an accurate and synthesized computational analysis can be successfully developed in order to access the groundwater flow of the study region. R E S U M O O aumento do consumo de água, associado à ocupação urbana desordenada, levou a um cenário de superexplotação de fontes superficiais e subterrâneas no Distrito Federal. Com a expansão das áreas urbanas, a água subterrânea tem desempenhado um papel importante no abastecimento público, evidenciando a necessidade de se aprofundar o conhecimento sobre o arcabouço hidrogeológico local. Neste sentido, este trabalho apresenta um modelo geológico conceitual da Bacia do Córrego do Ribeirão Tortinho. O principal objetivo deste relatório é organizar os dados disponíveis e apresentá-los na forma de um modelo conceitual que possa subsidiar a construção de um modelo numérico de fluxo de água subterrânea. Para simplificar a representação da estrutura hidrogeológica, rochas e materiais inconsolidados com parâmetros hidráulicos e propriedades texturais similares foram agrupados para formar unidades hidrostratigráficas. Seis unidades foram diferenciadas e suas propriedades e atributos foram discutidos. O domínio poroso é representado pelas unidades hidrostratigráficas I, II, III e IV, caracterizadas por latossolos, plintosolos, cambissolos e gleissolos, respectivamente. As unidades rochosas do Grupo Paranoá foram atribuídas às outras duas unidades hidroestratigráficas. Quartzitos e metarritmitos (Formações Ribeirão da Contagem e Serra da Meia Noite, respectivamente) formam a unidade hidrostratigráfica V, enquanto as ardósias (Formação Ribeirão do Torto) formam a unidade VI. Através deste arranjo sistemático, uma análise computacional precisa e sintetizada pode ser desenvolvida com sucesso para representar o fluxo de água subterrânea da região de estudo. Palavras-chave: fluxo subterrâneo, modelo geológico conceitual, gestão em recursos hídricos.